EDITORIAL: Under the pandemic siege - Philip Cass (Asia Pacific Network, 2020)
It is possible that future generations will think that BC stands for Before Coronavirus—and possibly that AD stands for After the Donald. All joking aside, here in Aotearoa New Zealand we have been far luckier than most countries, with early and decisive action by Prime Minister Jacinda Ardern and her advisers rapidly bringing the pandemic threat under control. Several Island nations remain COVID-free, thanks again to early intervention and strong measures, including border control. In countries which did not react properly, the results have been catastrophic. The Centre for Disease Control and Prevention (CDC, 2019) has predicted that the appalling death toll in the United States will reach and possibly surpass 250,000 by the time Donald Trump is finally ejected from the White House. Comparatively safe as we are in New Zealand, this is still the second edition of Pacific Journalism Review we have produced with COVID-19 in the background and even when the pandemic is over, or at least brought under control, we will still be threatened by a host of challenges—not least that of climate change, which has already forced internal migration in Papua New Guinea and Fiji and threatens to do the same in the ASEAN region, with its incomparably larger population.